Arabic Language Learning Strategies in Elementary Education: Enhancing Student Motivation and Comprehension through Pedagogical Innovation - Fadhilah, Lilik Nur (Transpublika Publisher, 2025)
Arabic language instruction at the elementary level constitutes a crucial foundation for subsequent linguistic development; however, classroom practice is frequently constrained by limited student engagement and the predominance of monotonous instructional techniques. This study examines the implementation of innovative pedagogical strategies at MI Salafiyah Syafi’iyyah Bandung III and evaluates their implications for learners’ motivation and vocabulary acquisition. Employing a descriptive qualitative design, data were obtained through participant observation, in-depth interviews with teachers and students, and analysis of relevant instructional documents. The findings indicate that the incorporation of language-based games and visually enriched learning media fostered a more interactive classroom climate, which in turn enhanced student participation and attendance. Moreover, these strategies were found to facilitate learners’ comprehension and retention of basic vocabulary and simple sentence patterns. The study further reveals that learning approaches aligned with children’s cognitive and affective characteristics can mitigate common obstacles in early foreign language instruction. Overall, the results underscore the importance of pedagogical innovation in revitalizing Arabic language learning in madrasas and suggest that context-sensitive, child-centered strategies can serve as an effective catalyst for improving both learner motivation and foundational language competence.